Reframing conservation audiences from individuals to social beings - L. Thomas‐Walters; V. Cologna; E. deLange; J. Ettinger; M. Selinske; M. S. Jones (Conservation Letters)
Abstract Environmental practitioners often develop communications and behavior change interventions that conceptualize individuals as consumers or as other limited, standalone personae. This view neglects the role of conservation audiences as social beings with complex social relationships and networks, potentially resulting in lost opportunities to increase the effectiveness of conservation interventions. We offer a reframing of individuals as members of social networks who can influence others through their many different societal roles. This framing may help individuals recognize their potential to affect large‐scale societal structures and empower them to contribute to systemic changes. In practice, conservation organizations might increase the impact and reach of their behavioral interventions by targeting social referents (individuals or groups who people reference for accepted and desired behaviors) and leveraging interpersonal relationships. This includes encouraging individuals to make use of their networks to discuss issues such as biodiversity loss with a variety of acquaintances to normalize them as a topic of conversation. We argue that organizations can leverage the power of social networks to amplify change and promote the message that people change the world through their social ties, thereby inspiring audiences to further engage in conservation behaviors.